Production Chain and COVID-19 Disruption: Sustainability via Flexibility Framework a Case of the Beverage Industry - Adedugba, Adebayo; Adeyemo, Felicia; Oreagba, Oluwakemi (Yugoslav Journal of Operations Research; Vol 35 No 1 (2025), 2024)
The pandemic has uncovered the weakness and volatility of production chains. The study examined the implication of corona-virus on the production chain functionality in a beverage production firm in terms of sustainability and flexibility. The study also evaluated a contextual analysis of an organization, the impact of the corona-virus outbreak, and the challenges the organization encountered. A purposive method was utilized as an information-gathering source from 200 participants. The outcome shows that the pandemic prompted critical disturbances such as the deficiency of resources/extra parts, accessibility of transportation, accessibility of work, and safety guidelines. The study also postulates that there is a need to re-design the production chain to be more flexible and resilient by providing recuperation plans (anticipation, choice of supply, modeling, observing) that consider measures in various echelons. Given this, a prescribed optimal procedure was suggested for the contextual analysis by considering inward, outward, and technological bottlenecks during the pandemic. A portion of the designated procedure and the optimization of the production chain can be considered and utilized in the other sectors.